Development and validation by the target audience of an educational booklet for people with diabetes mellitus. - Lidiane Jácome dos Santos, Carla; dos Santos Silva, Alex; Marques Pereira de Melo Alves, Adriana; Simplício de Oliveira, Patrícia; dos Santos Oliveira, Jacira; Lopes Costa, Marta Miriam; de Andrade, Lidiane Lima (Rev Rene, 2025)
Objective: to develop and validate the content and appearance by the target audience of an educational booklet for promoting health among people with diabetes mellitus. Methods: methodological study involving individuals diagnosed with type 2 diabetes mellitus. Instruments with psychometric properties were used to verify content and appearance, ensuring the reliability and interpretability of the results. The Content Validity Index and Appearance Validity Index were used to mediate data analysis. Results: in the content and appearance validation stage, there was a positive agreement of over 95%. In the content analysis, modifications were recommended for items related to the objective and structure. while in the appearance evaluation, suggestions focused on adjustments to the illustrations and layout. Conclusion: the educational booklet, which focused on promoting health and quality of life, was validated by the target audience in terms of both content and appearance. Contributions to practice: the validated version of the educational material is relevant for the therapeutic mana- gement of people with diabetes, and it also represents a potential resource for strengthening health promotion actions.